KATO NAN AMPEK" UNTUK MEMBENTUK KARAKTER - Fauziah Fauziah; Silvianetri Silvianetri (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2026)
Student character is a crucial component of the Indonesian education system, which should not rely solely on formal instruction but also on the instillation of local values that reflect the culture of the community. The public continues to debate issues of character development in children, with various media and discussions focusing on deviant student behavior, such as dishonesty and plagiarism. To meet the national education goals of building character and creating a dignified human culture, character education must encompass all aspects of the school environment. Literature research suggests that character education instills moral qualities such as honesty and respect by involving all aspects of education. Minangkabau traditional values, particularly Kato Nan Ampek, play a crucial role in this process by emphasizing ethical communication and interaction that adheres to social norms. Kato Nan Ampek not only serves as a behavioral guide but also helps preserve traditional Minangkabau values. Character education based on Kato Nan Ampek aims to help students develop effective communication skills while preserving their ethnic identity. Character education, when implemented consistently, has the potential to produce a generation that is intellectually developed, possesses noble character, and is ready to contribute positively to society.